2014
DOI: 10.1002/em.21912
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of 1‐methylpyrene and 1‐hydroxymethylpyrene in chinese hamster V79‐derived cells expressing both human CYP2E1 and SULT1A1

Abstract: 1-Methylpyrene (1-MP) is a widespread pollutant that is carcinogenic in animals following metabolic activation. Previous studies have shown that benzylic hydroxylation of 1-MP, catalyzed by multiple CYP isoforms, gives rise to 1-hydroxymethylpyrene (1-HMP), which becomes bioreactive following further metabolism by various sulfotransferase (SULT) isoforms. However, the mutagenic and chromosome damaging effects of 1-MP and 1-HMP in mammalian cells have not been investigated. In this study a Chinese hamster V79-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…As a chromogenic indicator for nicotinamide adenine dinucleotide (NADH) and cell viability (Ishiyama et al, 1997), CCK-8 values correspond well with cell numbers, as previously reported (Jiang et al, 2015). As a chromogenic indicator for nicotinamide adenine dinucleotide (NADH) and cell viability (Ishiyama et al, 1997), CCK-8 values correspond well with cell numbers, as previously reported (Jiang et al, 2015).…”
Section: Cytotoxicity Assay Associated With the Micronucleus Testsupporting
confidence: 84%
See 1 more Smart Citation
“…As a chromogenic indicator for nicotinamide adenine dinucleotide (NADH) and cell viability (Ishiyama et al, 1997), CCK-8 values correspond well with cell numbers, as previously reported (Jiang et al, 2015). As a chromogenic indicator for nicotinamide adenine dinucleotide (NADH) and cell viability (Ishiyama et al, 1997), CCK-8 values correspond well with cell numbers, as previously reported (Jiang et al, 2015).…”
Section: Cytotoxicity Assay Associated With the Micronucleus Testsupporting
confidence: 84%
“…1-HMP is an intermediate metabolite of 1-MP, formed through hydroxylation of the methyl carbon of 1-MP by a CYP enzyme. 1-HMP is further activated through sulfo-conjugation by a SULT (e.g., SULT1A1) for the formation of 1-sulfooxymethylpyrene (1-SMP), which is electrophilic, capable of forming adducts with DNA and proteins (Bendadani et al, 2014b), and inducing mutagenic responses (Jiang et al, 2015). Benzo[a]pyrene is primarily activated to benzo[a]pyrene-7,8-dihydrodiol-9,10-epoxide (BPDE) by CYP1A1 and 1B1 (Shimada et al, 2001), with the additional involvement of microsomal epoxide hydrolase, an enzyme ubiquitously expressed in all cell lines studied, including V79 cells (Glatt et al, 1990a).…”
Section: Introductionmentioning
confidence: 99%
“…Bioactivation of 1-HMP in humans can be catalyzed by several SULTs, of which human SULT1A1 is reported to be by far the most efficient followed by 1E1. Furthermore, SULT1A2, 1A3, 1B1, 1C2, 1C3, 2A1, and 2E1 also convert 1-HMP into a genotoxic metabolite, but to much lower extents (Meinl et al 2002;Meinl et al 2013;Jiang et al 2015). The antibody raised against SULT1A used in the present study detects SULT1A1 and 1A3 with a similar affinity.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, SULT1A2, 1A3, 1B1, 1C2, 1C3, 2A1, and 2E1 also convert 1-HMP into a genotoxic metabolite, but to much lower extents (Meinl et al 2002;Meinl et al 2013;Jiang et al 2015). Furthermore, SULT1A2, 1A3, 1B1, 1C2, 1C3, 2A1, and 2E1 also convert 1-HMP into a genotoxic metabolite, but to much lower extents (Meinl et al 2002;Meinl et al 2013;Jiang et al 2015).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation